Tracking the luminal exposure and lymphatic drainage pathways of intravaginal and intrarectal inocula used in nonhuman primate models of HIV transmission. - Jeremy Smedley; Baris Turkbey; Marcelino L Bernardo; Gregory Q Del Prete; Jacob D Estes; Gary L Griffiths; Hisataka Kobayashi; Peter L Choyke; Jeffrey D Lifson; Brandon F Keele (PLoS ONE)
Over 80% of sexual HIV-1 transmissions originate from a single viral variant, but the underlying basis for this transmission bottleneck remains to be elucidated. Nonhuman primate models of mucosal virus transmission allow opportunities to gain insight into the basis of this mucosal bottleneck. We used simulated inocula consisting of either non-infectious vital dye or contrast dye with non-invasive magnetic resonance imaging (MRI) to visualize mucosal exposure and passive lymphatic drainage patterns following vaginal and rectal exposures in Indian origin rhesus macaques. Results revealed a limited overall distance of dye coverage from the anal verge following 1 ml (n = 8) intrarectally administered, which greatly increased with a 3 ml (n = 8) volume. Intravaginal dye exposure using 2 ml revealed complete coverage of the mucosa of the vagina and ectocervix, however dye was not detectable in the endocervix, uterus, fallopian tubes or ovaries in nuliparous sexually mature rhesus macaques (n = 9). In addition, following submucosal and intranodal injections of vital dye or MRI contrast dye in the rectum (n = 9), or distal and proximal vagina (n = 4), the lymphatic drainage pathways were identified as first the internal then common iliac chain followed by para-aortic lymph nodes. Drainage from the distal descending colon (n = 8) was via the para-colonic lymph nodes followed by the inferior mesenteric and para-aortic lymph nodes. Analysis after vaginal challenge with infectious SIVmac239 followed by euthanasia at day 3 revealed a pattern of viral dissemination consistent with the imaging results. These results provide insights into potential patterns of viral dissemination that can help guide efforts to better elucidate the earliest events of virus transmission and potential intervention strategies.